Roles of Nursing in the Management of Geriatric Cardiovascular Diseases - Zhang, Chunzhi; Xiang, Congling; Tian, Xin; Xue, Jun; He, Gengxu; Wu, Xueliang; Mei, Zubing; Li, Tian (Frontiers in Medicine, 2021)
Nurse occupies the largest parts of cardiovascular healthcare services, whereas the effect of nursing on cardiovascular healthcare system is not in proportion with their number. We aimed to make a narrative review of recent publications regarding the nursing management in geriatric cardiovascular disease (CVD). The authors searched the PubMed and Embase (between Jan 1, 1950 and Jan 17, 2020) and make a narrative review. Old people with CVD, mainly including myocardial ischemia and heart failure are enrolled. The authors extract the viewpoints of original articles. Nursing management can improve the outcomes of myocardial ischemia and heart failure. It plays as pivotal roles in the recovery, rehabilitation, and outcomes of geriatric CVD, especially chronic heart diseases. Taken together, this paper compiled here is devoted to the current status of cardiovascular nursing and may facilitate future research and progress in geriatric CVD.